2014
DOI: 10.4041/kjod.2014.44.3.128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxicity and cytotoxicity in the buccal epithelial cells of patients undergoing orthodontic treatment with three light-cured bonding composites by using micronucleus testing

Abstract: ObjectiveThis study evaluated the cytotoxicity and genotoxicity of fixed orthodontic treatment with three different light-cured orthodontic bonding composites by analyzing micronucleus (MN) formation in the buccal mucosa during a 6-month period.MethodsThirty healthy volunteers were selected from consecutive patients referred for orthodontic treatment. Equilibrium 2 brackets and molar tubes (Dentaurum) were bonded with three different light-cured orthodontic bonding composites-Transbond XT (3M Unitek), Kurasper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
2
17
3
4
Order By: Relevance
“…[6] Therefore, we evaluated the genotoxic and cytotoxic effects of orthodontic treatment on human oral mucosa cells in such a setting.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Therefore, we evaluated the genotoxic and cytotoxic effects of orthodontic treatment on human oral mucosa cells in such a setting.…”
Section: Discussionmentioning
confidence: 99%
“…They have concluded that chewing gutkha along with smoking is more dangerous for human health as it hastens the incidence of OSMF. Toy et al [20] evaluated the cytotoxicity and genotoxicity of fixed orthodontic treatment with three different light-cured orthodontic bonding composites by analyzing MN formation and nuclear alterations, such as KR, KL, and BNs, in the buccal mucosa during a 6-month period. Parameters were scored under light microscope using acridine orange stain.…”
Section: Projects For the Apoptosis And Buccal Cell Micronuclei Assaymentioning
confidence: 99%
“…Itaconic acid is a component of natural origin and it is supposed that will not induce genotoxicity. (Meth)acrylate monomers are reported in the literature to exhibit genotoxic effects [24][25][26][27][28][29][30] . Furthermore, Dearfield et al 55 showed that acrylates are generally more potent to induce mutations, abberations and micronuclei than methacrylates, although this appears to be structure-related (dependent upon number of functional vinyl groups and the length of oxyethylene chains).…”
Section: Comet Assaymentioning
confidence: 99%
“…Although many HEMA-based hydrogels are generally considered to be non-toxic and have been used in biomedical applications [21][22][23] , the information on their safety is still incomplete. HEMA, as (meth)acrylate monomer, is capable to induce various adverse effects at cellular level, such as oxidative stress, cell cycle disturbance and apoptosis [24][25][26][27] . Table 1 shows the results of different in vitro studies which have demonstrated that HEMA is a potent mediator of DNA damage, at concentrations ranging from micromolar to millimolar.…”
Section: Introductionmentioning
confidence: 99%